Osteointegration in Cranial Bone Reconstruction: A Goal to Achieve. Issue 4 (6th June 2016) - Sprio, Simone; Fricia, Marco; Maddalena, Giuseppe F.; Nataloni, Angelo; Tampieri, Anna
Background: The number of cranioplasty procedures is steadily increasing, mainly due to growing indications for decompressive procedures following trauma, tumor or malformations. Although autologous bone is still considered the gold standard for bone replacement in skull, there is an urgent need for synthetic porous implants able to guide bone regeneration and stable reconstruction of the defect. In this respect, hydroxyapatite scaffolds with highly porous architecture are very promising materials, due to the excellent biocompatibility and intrinsic osteogenic and osteoconductive properties that enable deep bone penetration in the scaffold and excellent osteointegration. Osteointegration is here highlighted as a key aspect for the early recovery of bone-like biomechanical performance, for which custom-made porous hydroxyapatite scaffolds play a major role. There are still very few cases documenting the clinical performance of porous scaffolds following cranioplasty. Methods: This paper reports 2 clinical cases where large cranial defects were repaired by the aid of porous hydroxyapatite scaffolds with customized shapes and 3D profiles (Fin-Ceramica, Faenza, Italy). Results: In the long term (i.e., after 2 years), these scaffolds yielded extensive osteointegration through formation and penetration of new organized bone. Conclusions: These results confirm that porous hydroxyapatite scaffolds, uniquely possessing chemico-physical and morphological/mechanical properties very close to those of bone, can be considered as a tool to provide effective bone regeneration in large cranial bone defects. Moreover, they may potentially prevent most of the postsurgical drawbacks related to the use of metal or plastic implants.